MRI guided stereotactic radiotherapy for locally advanced pancreatic cancer - Heerkens, Hanne D (Br J Radiol, 2018)
OBJECTIVE: We want to explore the safety and technical feasibility of MRI-guided stereotactic radiotherapy for locally advanced pancreatic cancer. METHODS: A custom-made abdominal corset was manufactured to reduce breathing induced tumour motion. Delineation of the tumour and organs at risk (OARs) was performed on CT and multiparametric MRI. Tumour motion was quantified with cine MRI. After treatment planning, the static dose distribution was convolved with the cine MRI-based motion trajectory to simulate the delivered dose to the tumour and OARs. Stereotactic body radiation therapy (SBRT) was carried out up to a dose of 24 G in three fractions in 1 week. RESULTS: From July 2013 to January 2016, 20 patients were included. Tumours and OARs were clearly visible with contrast-enhanced CT and MRI. After simulation of the delivered dose taking the motion into account, an adequate target coverage was achieved with acceptable dose in the OARs. No Grade3 or higher treatment related toxicity was observed. CONCLUSION: MRI-guided SBRT for pancreatic cancer is technical feasible and safe, with no treatment related grade ≥3 toxicity. New strategies are applied, including an individual corset to reduce breathing motion, MRI-based delineation and simulation of motion-integrated dose distributions. ADVANCES IN KNOWLEDGE: This article is the first to describe an MRI-integrated workflow in SBRT for locally advanced pancreatic cancer. In addition, it demonstrated that SBRT with an abdominal corset to reduce tumour motion is feasible and safe. TRIAL REGISTRATION: This trial was registered at www.clinicaltrials.gov (NCT01898741) on July 9, 2013.